2014
DOI: 10.1007/s00192-014-2425-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of thumb and index finger placement in manual perineal protection

Abstract: In a biomechanical assessment with simulation of vaginal delivery, exact placement of fingertips on the perineal skin, together with their co-ordinated movement, plays an important role in the extent of reduction of perineal tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…Indeed, computational analysis revealed that the degree of reduction in perineal strain at the fourchette is a determinant of where the thumb and index finger are placed on the perineum as well as the distance and direction of their medial movements. Based on measures of maximum perineal strain, minor alterations in these parameters were associated with a gradual reduction in the maneuver’s efficacy . Interestingly, all the respondents who provided correct and complete information about the MPP technique had <5 years’ work experience in maternity care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, computational analysis revealed that the degree of reduction in perineal strain at the fourchette is a determinant of where the thumb and index finger are placed on the perineum as well as the distance and direction of their medial movements. Based on measures of maximum perineal strain, minor alterations in these parameters were associated with a gradual reduction in the maneuver’s efficacy . Interestingly, all the respondents who provided correct and complete information about the MPP technique had <5 years’ work experience in maternity care.…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly achieved by a reduction in the transverse perineal tension using the accoucheur’s thumb and index finger alongside the vaginal opening . Subsequent computational biomechanical studies showed that such maneuver can produce up to a 30% reduction in relative tension in the perineal region, dependent on the precision of its execution . Indeed, the maneuver is most effective when the thumb and index finger were applied 12 cm apart, 2 cm anterior to the posterior fourchette and approximated medially by 1 cm on either side.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One would expect such confounding factors to be balanced in a suitably powered RCT. Moreover, there are several techniques of MPS that might have different degrees of effectiveness in supporting the pelvic floor …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are several techniques of MPS that might have different degrees of effectiveness in supporting the pelvic floor. 60…”
Section: Interpretation Of Findingsmentioning
confidence: 99%